Plan de revitalización urbana a través del diseño de espacio público en el interior de las manzanas, ubicadas en el centro tradicional de la ciudad de Armenia (2021)
Armenia Quindío has been a city that over time has evolved to the present day, as it is still in a stage of expansion both at the territorial and economic level, however, of the various sectors that it has, the most prominent It has been the central sector, which enjoys being an attractor for those who request a product, service or need. It can be said that this area is controversial due to its various problems, such as prostitution, the increase in street vendors, insecurity, high traffic and a high deficit of public space, factors that lack solutions and the situation worsens day by day. Problems similar to those in Armenia today occur in the world, which is why we seek to reference projects that contribute to economic development and improve the quality of life or habitat of a space. Places such as Neals Yeard - London, the interior of Waldorf's block in Spain and the heart of Pablo de La Torre's block in Argentina, are pioneers in the idea of recovering the existing voids in the center of a residential or commercial complex, open the possibility of interacting with new spaces that enhance other benefits at the municipal level. This is nourished by exploring the opinions of architects who see these alternatives as optimal to guarantee solutions to major problems in a city, however, the opportunity is opened to know the opinion of those who have knowledge or who have a commercial presence in the center of Armenia and They make evident the needs that this place requests in view of its social and spatial problems. Open skies is the main route - public space that the quindio´s capital has, connects the Plaza de Bolívar with Sucre Park, but taking into account that the CAM administrative center has a potential for permanent spaces, highlighting the great economic demand that surrounds it. It can be said that there is a gap that disconnects the social dynamics present in career 14 with this other sector, making it in some way exclusive. That is why, through various analyzes, existing internal voids are evidenced in two blocks where valuable assets such as the El Lobo Building and the Presbyterian Church are present, whose infrastructure is in optimal condition, but remain in oblivion.Taking this into account, it is evident that the blocks between Carrera 14 and Carrera 16 and Calle 16 and 17 act as an attractor and economic corridor where people move from the open skies trade to the CAM Finally, there are these great factors to create the urban revitalization project, intervening in places with less residential / commercial impact and creating a new public space in the sector that function as a corridor, memorial, economic and gastronomic attractor, welcoming and enhancing existing commerce. in the city center, in this way we connect open skies with the CAM administrative center and its surroundings.